Storytelling y comunicación multidireccional: una estrategia formativa para la era digital (Ensayos) - Hermann Acosta, Ernesto Andrés (2020)
This research work focused on reflecting how Storytelling constitutes a strategy that drives the transition from a unidirectional communication model to a multidirectional one, as well as the scope it has to promote the configuration of an open, flexible education model. Interactive, in order to obtain the research results, a review of the state of the art in study areas such as Storytelling, dialogic and multidirectional communication and the application of Storytelling in the educational field was carried out. The methodological treatment used the search for primary and bibliographic sources from high-impact repositories. The foregoing allowed us to conclude that the use of Storytelling based on non-artefactual communicational and pedagogical considerations favors the consolidation of open, dialogic and multidirectional communication and education schemes.